Efektivitas Penggunaan Jenis Pelapis Terhadap Kualitas Dan Masa Simpan Buah Mangga (Mangifera indica L.) Varietas Gadung Klon 21 - Chabib IS., Muhammad (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
The objective of the research is to determine the effect of fruit maturity and surface coating material on storagelife and quality of fruit. The research has carried out at Situbondo and Polytechnic of Jember, since May to September 2005. The design used in this research was Factorial Completely Randomized with three replications. The first factor was fruit maturity i.e.:  105,  110, and 115 days after full bloom (dafb). The second factor was the kind of surface coating materials i.e.: bee wax, palm oil, and glutinous rice starch. The research datas were variance analysed and the significance among treatment mean values were determined by Least Significant  Difference (LSD)  at the p 0.05 level. The result showed that maturity influenced: the carbon dioxide release at 7,  8, and 9 days,  the ethylene release at 9 days, weight loss, total soluble solids and sensory. There were interaction effects of maturity and coating material on total acid, reducing sugars, ascorbic acid, and storage life.